Determination of Subsurface Structure with Magnetic Method - Indah Gumilang Dwinanda (LPPM Institut Studi Islam Sunan Doe, 2024)
The magnetic method is one of the methods used in geophysical engineering. Measurements using the magnetic method that are mostly carried out are by using a PPM (Proton Precession Magnetometer). The application of the magnetic method is often used in preliminary exploration of petroleum, geothermal, and mineral deposits and can be applied to prospecting for archaeological objects. The purpose of this study was to determine the subsurface layers using the magnetic method as an initial survey with the hope of being able to apply magnetic method theory in practice in the field before carrying out other, more complex surveys.